2019
DOI: 10.3390/app9204432
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Nutrient Disorders of Cannabis sativa

Abstract: Essential plant nutrients are needed at crop-specific concentrations to obtain optimum growth or yield. Plant tissue (foliar) analysis is the standard method for measuring those levels in crops. Symptoms of nutrient deficiency occur when those tissue concentrations fall to a level where growth or yield is negatively impacted and can serve as a visual diagnostic tool for growers and researchers. Both nutrient deficiency symptoms and their corresponding plant tissue concentrations have not been established for c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
54
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 41 publications
(66 citation statements)
references
References 10 publications
11
54
0
1
Order By: Relevance
“…A study conducted by [16] also concluded that hemp growth response to fertilizer N was negligible in soils rich in N. Due to differences in environmental conditions and methodologies, the stem biomass per unit of N fertilization cannot be accurately determined from literature data and therefore warrants more investigation. A recently conducted study reported that N deficiency symptoms were observed in greenhouse-grown hemp for CBD when the N content in the leaf tissue analysis was 1.62% [68]. However, more research is needed to evaluate the effect of N application on the yield of seed and CBD hemp varieties under field conditions.…”
Section: Effect Of Nitrogenmentioning
confidence: 99%
See 4 more Smart Citations
“…A study conducted by [16] also concluded that hemp growth response to fertilizer N was negligible in soils rich in N. Due to differences in environmental conditions and methodologies, the stem biomass per unit of N fertilization cannot be accurately determined from literature data and therefore warrants more investigation. A recently conducted study reported that N deficiency symptoms were observed in greenhouse-grown hemp for CBD when the N content in the leaf tissue analysis was 1.62% [68]. However, more research is needed to evaluate the effect of N application on the yield of seed and CBD hemp varieties under field conditions.…”
Section: Effect Of Nitrogenmentioning
confidence: 99%
“…Hemp plants suffering from P deficiency show visual symptoms including stunted growth and development of reddish-purple color in the leaf due to anthocyanin pigment formation [72]. In a recent study, leaf tissue analysis of P was reported to be 0.09% for P deficient CBD hemp plants grown under greenhouse conditions [68].…”
Section: Effect Of Phosphorusmentioning
confidence: 99%
See 3 more Smart Citations